MEMBANGUN SISTEM INFORMASI PENJUALAN OBAT DI APOTIK SEJATI MALANG MENGGUNAKAN MICROSOFT VISUAL BASIC 6 - Mumpuni, Indah Dwi; Sitorus, Jeffr i Bastian (DINAMIKA DOTCOM, 2012)
The development of information technology brought significant changes in the development of world civilization.  At True Pharmacies,  all management  systems run  manually,  so  the constraint that  often arises  is common miscalculation financial  statements and require long lead time, thereby reducing the efficiency of the work. This research aims to generate sales of drug information systems using Microsoft Visual  Basic that  is  expected to assist the data processing becomes faster and easier in terms of making drug sales report.  The information system is also expected to facilitate pharmacists in the process of checking the critical drug stocks and report the sale and purchase  of drugs.  It  can improve the quality of service to consumers.Key words : application, drug sales, information systems, pharmacy true.